Identification of components in Kazakhstan honeys that correlate with antimicrobial activity against wound and skin infecting microorganisms - Pauline McLoone; Aizhan Zhumbayeva; Sofiya Yunussova; Yerkhat Kaliyev; Ludmila Yevstafeva; Susan R. Verrall; Julie Sungurtas; Ceri Austin; J. Will Allwood; Gordon J. McDougall (Springer Science and Business Media LLC, 2021)
Anti-microbial activity and chemical composition of 12 Kazakhstan honeys and medical-grade manuka honey were investigated. Well diffusion and broth culture assays showed highest susceptibility for MRSA (clinical isolate) and Enterococcus faecalis (ATCC 19433). Buckwheat & multi-floral Kazakhstan honeys exhibited highest activity; buckwheat and manuka had highest total phenols. Non-targeted LC identified components correlating with activity: hydroxyphenyl acetic acid, p-coumaric acid, (1H)–quinolinone, and abscisic acid.
Keywords: Antimicrobial; Enterococcus faecalis; Staphylococcus aureus; Microbiology; Biology; Manuka Honey; Food science; Agar; Bacteria; Genetics; type of access: open access